2019
DOI: 10.7717/peerj.7067
|View full text |Cite
|
Sign up to set email alerts
|

Identification of primary genes in glomeruli compartment of immunoglobulin A nephropathy by bioinformatic analysis

Abstract: The current study is aimed to explore the specific genes which are responsible for the manifestation of Immunoglobulin A nephropathy (IgAN). Gene expression profiles GSE37460, GSE93798 and GSE104948 were analyzed using biological informatics methods to identify differentially expressed genes (DEGs) in IgAN glomeruli samples which were then compared to normal control samples. Subsequently, the DEGs were overlapped to explore genes with significant expression in at least two profiles. Finally, the enrichment ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 32 publications
1
5
0
Order By: Relevance
“…Re-analyzing and integration of omics-based expression profiles could be an advantageous tactic to catch a holistic view of the involving genes and miRNAs in the IgAN pathogenesis. Until now, several re-analyzes have been performed on the IgAN related expression profiles, mostly on kidney tissue samples of the patients [25][26][27][28].…”
Section: Discussionmentioning
confidence: 99%
“…Re-analyzing and integration of omics-based expression profiles could be an advantageous tactic to catch a holistic view of the involving genes and miRNAs in the IgAN pathogenesis. Until now, several re-analyzes have been performed on the IgAN related expression profiles, mostly on kidney tissue samples of the patients [25][26][27][28].…”
Section: Discussionmentioning
confidence: 99%
“…For instance, in one experiment after reanalysis of two IgAN datasets, including GSE73953 and GSE93798, tumor nephrotic factor ( TNF ) and mitogen-activated protein kinase ( MAPK ) pathways were introduced as the key involved pathways in the IgAN pathogenesis [ 13 ]. Similarly, in another experiment, after analysis of three datasets, including GSE37460, GSE93798 and GSE104948, Miraji et al, revealed the association of “extracellular matrix receptors interaction pathways”, “extracellular matrix expansion” and “inflammatory mechanisms” with the pathogenesis of IgAN [ 14 ]. By construction of a PPI network among the overlapped DEGs and considering the degree of connectivity between the genes, the authors introduced several hub genes with therapeutic potentials including FN1 , ITGB2 , FCER1G and PTPRC [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, in another experiment, after analysis of three datasets, including GSE37460, GSE93798 and GSE104948, Miraji et al, revealed the association of “extracellular matrix receptors interaction pathways”, “extracellular matrix expansion” and “inflammatory mechanisms” with the pathogenesis of IgAN [ 14 ]. By construction of a PPI network among the overlapped DEGs and considering the degree of connectivity between the genes, the authors introduced several hub genes with therapeutic potentials including FN1 , ITGB2 , FCER1G and PTPRC [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…For instance, in one experiment after reanalysis of two IgAN datasets, including GSE73953 and GSE93798, tumor nephrotic factor (TNF) and mitogen-activated protein kinase (MAPK) pathways were introduced as the key involved pathways in the IgAN progression (13). Similarly, in another experiment, after analysis of three datasets, including GSE37460, GSE93798 and GSE104948, Miraji et al, revealed the association of "extracellular matrix receptors interaction pathways", "extracellular matrix expansion" and "in ammatory mechanisms" with the progression of IgAN (14). By construction of a PPI network among the overlapped DEGs and considering the degree of connectivity between the genes, the authors introduced several hub genes with therapeutic potentials including FN1, ITGB2, FCER1G and PTPRC (14).…”
Section: Discussionmentioning
confidence: 99%